2006
DOI: 10.1080/13547500600896791
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-3 and IGFBP-10 (CYR61) up-regulation during the development of Barrett's oesophagus and associated oesophageal adenocarcinoma: potential biomarkers of disease risk

Abstract: Dys-regulation of the insulin-like growth factor (IGF) system increases the risk of a number of malignancies. The aim of this study was to investigate the role of members of the IGF binding protein (IGFBP) superfamily in the development of oesophageal adenocarcinoma (EAC) and their possible use as markers of disease risk. Expression of IGFBP-2, IGFBP-3, IGFBP-4, and IGFBP-10/CYR61 was assessed using Real-Time-polymerase chain reaction (PCR) and immunohistochemistry in oesophageal tissues from Barrett's oesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…These two values were multiplied to yield a final staining score of between 0 and 12. In addition, cellular localisation was assessed (Di Martino et al, 2006). All sections were scored independently by two observers.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These two values were multiplied to yield a final staining score of between 0 and 12. In addition, cellular localisation was assessed (Di Martino et al, 2006). All sections were scored independently by two observers.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To allow semi-quantitative evaluation of protein expression, the epithelial component of each section was scored as described in the methods for intensity of immunoreactivity and percentage of epithelial cells stained (Di Martino et al, 2006) (Table 2).…”
Section: Immunolocalisation Of Myc/max/mad Network Proteins In the Prmentioning
confidence: 99%
“…5,6 Research shows that CYR61 may be regarded as both a suppressor and a promoter of cancer progression and tumour invasion. 14,17 Studies have shown that CYR61 can suppress carcinogenesis in nonsmall cell lung cancer or gastric carcinoma. 17,18 However, other studies have shown that CYR61 can enhance carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 CYR61 expression has been shown to be significantly higher in Barrett's oesophageal adenocarcinoma tissue than in Barrett's oesophageal tissue with no sign of cancer. 13,14 The significance of CYR61 expression and prognosis in ovarian epithelial cancer, however, remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Karaciğer metastazının tanı anında tümör invazyon derinliği, venöz invazyon ve lenf nodu metastazı varlığı ile yakın ilişkili olduğu gösterilmesine rağmen bu faktörlerin zayıf prediktif etkisi sebebi ile kullanımı kısıtlıdır (11)(12)(13). Bu sebeple tanı anında karaciğer metastazını predikte edecek farklı faktörler araştırılmıştır.…”
Section: Introductionunclassified